Learning and Technology Adoptions - Sebastian Scholz (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2010)
This essay studies the optimal timing for a firm to adopt a new process innovation in the presence of learning. A policy that has been implemented by governments throughout the world to reduce the cost level of infant industries with positive externalities, is to either subsidize the research of these technologies or their distribution. This model demonstrates how government interventions can affect the optimal timing for adoption of a new technology. Furthermore this essay makes predictions on how the effects change, when the total quantity that can be produced is fixed; the installations of wind powered energy plants exemplify this point. Depending on whether producer rents, consumer rents or early implementation are more important to the government, the model offers the appropriate tools to attain its objective.
urn:nbn:de:bvb:19-epub-11321-2
Keywords: C61; D42; H23; O12; 330; Learning; Process Innovation; Optimal Control; Infant industry; Innovation; Technologiewahl; Zeit; Innovationspolitik; Kontrolltheorie; Industriepolitik; Windenergie; Theorie